Teori Keadilan John Rawls Kritik Terhadap Demokrasi Liberal - anggara, sahya (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2013)
This article reexamines John Rawlsâs thought in formatting social order based on political liberalism. The discussion is significant in tracing the origins of thought on justice in the modern Western socio-ethical system. By bibliographical study of Rawlsâs works this study describes and analyzes the formats of Rawlsâs thought which places individuals as his fundamental reference of political thought. This article contextualizes Rawlsâs thought with what being happened in contemporary Indonesian cases.